Border water : the politics of U.S.-Mexico transboundary water management, 1945-2015 - Mumme, Stephen P. (The University of Arizona Press, 2023)
"This is the first scholarly study to detail the history and international politics of managing water flowing across the U.S.-Mexico border. Written from both a historical and political science perspective, the study's primary aim is to provide students and scholars with a reliable one-volume account of the history of binational cooperation on transboundary water management for the 70-year period under consideration. The historical narrative relies on archival sources, interviews, government documents, advocacy organizations' reports and correspondence, and a wide-ranging canvas of scholarly and popular press materials focused on transboundary water management. The author offers a unique periodization for better understanding developments in international cooperation through time"--